Case report: TMEM106B haplotype alters penetrance of GRN mutation in frontotemporal dementia family - Perneel, Jolien; Manoochehri, Masood; Huey, Edward D.; Rademakers, Rosa; Goldman, Jill (Frontiers in Neurology, 2023)
Frontotemporal dementia (FTD) is the second-most common young-onset dementia. Variants in the TMEM106B gene have been proposed as modifiers of FTD disease risk, especially in progranulin (GRN) mutation carriers. A patient in their 50s presented to our clinic with behavioral variant FTD (bvFTD). Genetic testing revealed the disease-causing variant c.349 + 1G > C in GRN. Family testing revealed that the mutation was inherited from an asymptomatic parent in their 80s and that the sibling also carries the mutation. Genetic analyses showed that the asymptomatic parent and sibling carry two copies of the protective TMEM106B haplotype (defined as c.554C > G, p.Thr185Ser), whereas the patient is heterozygous. This case report illustrates that combining TMEM106B genotyping with GRN mutation screening may provide more appropriate genetic counseling on disease risk in GRN families. Both the parent and sibling were counseled to have a significantly reduced risk for symptomatic disease. Implementing TMEM106B genotyping may also promote the collection of biosamples for research studies to improve our understanding of the risk-and disease-modifying effect of this important modifier gene.